THE IMPLEMENTATION OF MOBILE BANKING ON THE USE OF BSI MOBILE SERVICES BY CUSTOMERS (A STUDY BY TRIBAKTI ISLAMIC UNIVERSITY STUDENTS) - Hasanah, Putri Imroatul; Khairan; Anwar, Nur Rohim Al Mahrus (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
The development of digital technology has driven the transformation of financial services, including in the world of Islamic banking. Bank Syariah Indonesia (BSI) has launched BSI Mobile, a mobile banking application that combines financial, spiritual, and social functions to meet the needs of the younger generation, including students. Features such as zakat, infak, sedekah, and Quran readings demonstrate that BSI Mobile services are not only practical but also have Islamic value. With high smartphone penetration, students are a strategic group in adopting these services; however, understanding the implementation of digital Islamic services remains an important issue that requires further research. The method used in this study is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The research subjects are active users of BSI Mobile. To ensure data validity, the researcher conducted source and technique triangulation. This. The research findings indicate that the implementation of BSI Mobile by Bank Syariah Indonesia has been successfully adopted among students at Universitas Islam Tribakti Lirboyo Kediri. This is evident from the ease of access, transaction speed, and the variety of Islamic features offered, such as zakat, infaq, and Quran reading. These factors encourage students to actively use this digital service as part of their financial and spiritual needs. Additionally, the use of BSI Mobile reflects a transformation in customer behavior from conventional transactions toward digital transactions based on Islamic principles. Beyond providing convenience, BSI Mobile also plays a role in enhancing Islamic financial inclusion among the younger generation. The success of this implementation is further determined by strategic planning, technological infrastructure readiness, and effective user education from BSI